Inappropriate Medication Administration Practices in Canadian Adult ICUs: A Multicenter, Cross-Sectional Observational Study. (May 2013) - Kanji, Salmaan; Lam, Jason; Goddard, Rob D; Johanson, Christel; Singh, Avinder; Petrin, Lee; Coons, Patricia; McIntyre, Lauralyn A; Turgeon, Alexis F
BACKGROUND: Critically ill patients often receive multiple medications via continuous intravenous infusion. Coadministration of multiple medications through the same port of a venous access device often is necessary but requires an assessment of compatibility. OBJECTIVE: To describe the frequency of inappropriate coadministration of continuously infused medications via a Y-site and the use of intravenous catheters in patients in Canadian intensive care units (ICUs) in a multicenter, cross-sectional observational study. METHODS: Data pertaining to medication compatibility via Y-site infusion (medication combinations known to be incompatible or not known to be compatible), frequency of specific medications administered via continuous infusion, and catheter use (median number, location, and types of venous catheters) were collected from medical records of 434 patients in the ICUs of 13 teaching hospitals in Canada. RESULTS: Forty-six percent of patients were receiving 2 or more medication infusions simultaneously. Forty episodes of inappropriate coadministration of these infusions were identified in 37 patients. The prevalence of inappropriate coadministration of drugs via a Y-site port in all patients was 8.5% (95% CI 5.8–11.2). The prevalence of incompatible combinations via Y-site in patients with 2 or more medication infusions was 18.7%. Twenty-five of these 37 patients could have had their drug schedules rearranged into acceptable combinations, leaving 12 patients who would have required additional intravenous access to facilitate appropriate medication infusions. Median (range) number of central and peripheral venous access devices inserted per patient were 1 (0–4) and 1 (0–5), respectively. Seventeen of 95 patients with 2 or more central venous catheters could have had their medication infusions rearranged to render 1 catheter idle. CONCLUSIONS: Inappropriate Y-site combinations of medications continuously infused in Canadian ICUs are common. Management of medication infusions could, however, have been optimized in most of these situations.